Predicting Optimum Dilution Factors for BOD Sampling and Desired Dissolved Oxygen for Controlling Organic Contamination in Various Wastewaters - Hisham A. Maddah (International Journal of Chemical Engineering)
High biochemical oxygen demand (BOD) concentrations in water minimize oxygen availability, damage ecosystem biodiversity, impair water quality, and spoil freshwater. The increased level of BOD is an indication of severe organic pollution of freshwater. Thus, this study aims to establish empirical correlations between the 5-day biochemical oxygen demand (BOD5) and organic decomposition time to control organic pollution in various wastewater effluents. Ultimate biochemical oxygen demand (UBOD) and minimum and average BODt data sets along with their reaction rates were collected from earlier sampling analyses in the plants used for industrial, domestic (sanitary), and storm (surface) wastewater treatment. Average BOD5/COD ratios were then utilized to calculate existing 5-day dissolved oxygen (DO5) concentration for the estimation of experimental dilution factors (dfs) as a good start in sampling analysis to reach an optimum DO5 concentration. Moreover, the relationships between average BOD5 vs. COD, and BOD5 vs. DO5, were obtained based on the literature with 60–70% oxygen consumption rates required for organic decomposition. Results showed that such BOD5 relationships with time (power equations) or with COD (linear correlations) are helpful for wastewater engineers to generate valuable and accurate results for quality control, without the need to conduct laboratory experiments. The proposed regression equations would facilitate effluent quality assessment, allowing selection of optimal processes to control microbiological contamination or organic constituents in wastewaters.